Improved nonenzymatic glucose sensing properties of Pd/MnO2 nanosheets: synthesis by facile microwave-assisted route and theoretical insight from quantum simulations - Ponnusamy, Rajeswari; Gangan, Abhijeet; Chakraborty, Brahmananda; Late, Dattatray J.; Rout, Chandra Sekhar (Journal of Physical Chemistry B, 2018)
The electrocatalytic properties of manganese oxide (MnO2) can be improved significantly by making hybrids/composites with noble metals (Au, Pd). Here, efforts have been made to synthesize the MnO2/Au and MnO2/Pd nanocomposites by a facile, rapid microwave irradiation method. The products characterized by X-ray diffraction and transmission electron microscopy exhibited their tetragonal phase and nanosheet morphology. The efficiency of the prepared composite materials as glucose sensor was tested by cyclic voltammetry and chronoamperometry measurements, and the results are discussed. The study revealed that successful modification of MnO2 by Pd led to excellent sensing performance by the reduction of size and the synergistic effect between MnO2 and PdO, which expedites the electron transfer. Besides, the wide detection range, good selectivity, and stability demonstrate its robustness in the design of electrochemical sensor platform. To get theoretical insight into the excellent sensing performance of MnO2/Pd, we have performed detailed density functional theory simulations to explore the charge transfer and bonding mechanism of glucose on MnO2 and Pd/Au-doped MnO2 surface. Pd is bonded strongly on MnO2 and makes MnO2/Pd more conducting due to the enhancement of density of states near Fermi level. The higher binding energy of glucose and enhanced charge transfer from glucose to Pd-doped MnO2 compared to bare MnO2 infer that Pd-doped MnO2 possess superior charge-transfer kinetics, resulting in higher glucose sensing performance, which supports our experimental observations.